The effect of brain death and coma on gastric myoelectrical activity - Bor, Canan; Bordin, Dmitry; Demirag, Kubilay; Uyar, Mehmet (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Gastrointestinal motility problems and delayed gastric emptying in patients admitted to intensive care units are important because they can contribute to different problems. Herein we aimed to measure the changes in gastric myoelectrical activity with electrogastrography (EGG) following brain death (BD) and compare the results to those from patients in a deep coma without BD. Materials and Methods: Fifteen patients with BD and nine in a deep coma with a Glasgow Coma Score from 3 to 8 were included. An enteral nutrition solution was given via a nasogastric tube between 45 min of fasting and the postprandial periods. The mean dominant frequency (MnDF), normal gastric slow wave ratio (%), tachygastria and bradygastria (%), power ratio (PR: dominant power after test meal/fasting), and dominant frequency instability coefficient were evaluated. Results: The median of MnDF was determined 3.20±0.6 (BD) vs 3.05±0.5 (control), p>0.05. Patients with BD displayed tachygastria, particularly during the fasting state, with this disturbance decreasing during the postprandial period (from 41% to 15%). However, none of the differences between the groups were statistically significant. PR was pathologic in 4/15 (26.7%) patients in the BD group and 4/9 (44.4%) patients in the control group (p=0.288). Conclusion: Patients with coma or BD bouth might have gastric myoelectrical activity disturbances. BD does not show more severe disturbance than coma wihouth BD. EGG might be useful as a non-invasive and easy-to-use technology; however, it needs further improvement.